Rules on Home Office Work and Telework in Romania and in Hungary - Vallasek, Magdolna; Mélypataki, Gábor (Central European Journal of Comparative Law, 2020)
Pandemic crisis management requires new solutions that are not necessarily workable options in the traditional labour market. It is not about starting from scratch but about bringing to the fore legal institutions that have not been significant so far. This has had an unexpected effect on the labour law of Central European countries, as social partners fundamentally distrust atypical forms of work. This situation is also true for Romania and Hungary. In our study, we do not intend to present all forms, but only the two most important legal instruments in the labour market shaped by the pandemic; we analyse teleworking and home office work.